Colonoscopy: Quality Indicators. Issue 2 (February 2015) - Anderson, Joseph C; Butterly, Lynn F
Abstract : N/A: Effective endoscopic screening for colorectal cancer (CRC), one of the few preventable cancers, is dependent on the adequate detection and removal of potentially precancerous lesions. However, observed variation in colonoscopy performance in practice and outcomes has highlighted the need for consistent quality measures. Quality indicators or measures are tools that help to quantify health‐care processes and can aid in providing high‐quality health care. The primary colonoscopy quality indicator is the adenoma detection rate (ADR), which is defined as the proportion of an endoscopist's screening colonoscopies in which one or more adenomas have been detected. The risk of post‐colonoscopy CRC is inversely correlated with an endoscopist's ADR. However, ADR is dependent on other quality measures, including cecal intubation rates, withdrawal times, and quality of bowel preparation. Achieving suggested benchmarks for these other quality measures will aid the endoscopist in achieving the recently updated ADR benchmark of 25% in their practice. In addition, beyond ensuring adequate ADRs, endoscopists should have high compliance rates with guideline‐recommended and evidence‐based screening and surveillance intervals. Compliance with quality measures will ensure effective and safe CRC prevention and better patient outcomes.